2014
DOI: 10.1111/dpr.12064
|View full text |Cite
|
Sign up to set email alerts
|

Do Fair Trade Pricing Policies Reduce Inequalities in Coffee Production and Trade?

Abstract: This article assesses the Fair Trade pricing model for coffee, investigating the ability of minimum prices and a social premium to reduce price risk and remedy inequalities. It highlights some of the challenges involved in controlling prices. Inequalities exist among Fair Trade‐certified farmers; some are poorer than others, and the poorer ones typically produce less coffee. If Fair Trade succeeds in its aim of raising the prices received by farmers, this will benefit more those farmers producing greater volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 40 publications
0
7
0
2
Order By: Relevance
“…Some authors point their finger at the price mechanism of FT. For example, the FT minimum coffee price had not changed in the period 1988–2007 (Bacon, ; Valkila, ); indeed, over the same period, Bacon's findings reveal declining prices when discounted for inflation (Bacon, ), fueling allegations related to corporate capture of FT (Jaffee & Howard, ). The decline in the minimum price has shown that the same pricing system is closely linked to those market prices that it is intended to transform (Bacon, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors point their finger at the price mechanism of FT. For example, the FT minimum coffee price had not changed in the period 1988–2007 (Bacon, ; Valkila, ); indeed, over the same period, Bacon's findings reveal declining prices when discounted for inflation (Bacon, ), fueling allegations related to corporate capture of FT (Jaffee & Howard, ). The decline in the minimum price has shown that the same pricing system is closely linked to those market prices that it is intended to transform (Bacon, ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, limiting the value chain to the study of coffee and some cases of a few other certified products, the knowledge on the side of producers is limited in many directions. Discordant results demonstrate the complexity in finding information about the effectiveness of FT and represent an indicator of the limited awareness of the FT system mechanisms and limited identification with FT by producers (Valkila, ; Valkila & Nygren, ), two issues in which FT should invest more effort.…”
Section: Conclusion and Limitationsmentioning
confidence: 99%
“…In contrast, the absence of this institutional support can lead to VSS re‐enforcing social inequalities (Gómez Tovar et al ., ). There are several examples of VSS programs targeting risk‐tolerant farmer groups with pre‐existing production practices likely to meet applicable standards without any process ‘upgrading’ (Ibanez & Blackman, ; Valkila, ). This suggests VSS enrollment has less to do with active training, than it does with pre‐existing ‘strong institutional arrangements that deliver technical and commercial services’ to smallholders (Rueda & Lambin, : 11), including organizational capacity (Jena et al ., ).…”
Section: Global Value Chains and The Role Of Institutions In Rural Dementioning
confidence: 99%
“…Um dos focos diz respeito à relação entre a certificação e a qualidade do café. Pesquisas têm demonstrado que existem poucos incentivos para a qualidade do produto (RENARD, 2003;ZUNIGA, 2011) em um mercado onde o atributo qualidade também é essencial (GRIFFITHS, 2012;RAYNOLDS, 2009;RENARD, 2003RENARD, , 2005ZUNIGA, 2011;VALKILA;NYGREN, 2009; WEBER, 2011) nas relações comerciais. Já o outro foco está associado aos estudos dos impactos da certificação (BLACKMAN;RIVERA, 2011;MARE, 2008;POUND, 2009), com pesquisas motivadas por conhecer se a certificação realmente está cumprindo com os objetivos propostos pelos seus proponentes.…”
Section: Introductionunclassified